2010
DOI: 10.1007/s10157-010-0387-8
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in the treatment of acute cellular rejection of renal allograft with CD20-positive clusters in the infiltrate

Abstract: A 31-year-old woman with nephronophthisis received a cadaveric kidney transplant, and was immunosuppressed with cyclosporine, azathioprine and steroids. Twelve days after transplant a biopsy showed acute rejection with vascular damage. She was treated with 3 pulses of methylprednisolone and change of immunosuppression to mycophenolate mofetil and tacrolimus, without improving graft function. At day 21, a second biopsy showed accentuation of interstitial and vascular rejection. Antibody-mediated rejection was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Only case series were previously reported, and a systematic review of acute AMR treatment published in October 2012 showed insufficient data to guide treatment. 12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29]32 We showed that 1-year graft survival for AMR treated with IVIg, PE, and CS with or without rituximab was excellent, and we could not demonstrate a supplementary efficacy of rituximab by graft survival or our primary endpoint. An additional beneficial effect of PE and rituximab on graft survival was reported in a group of 12 patients receiving IVIg, PE, and rituximab (92%) as compared with a historical group of 12 patients receiving only IVIg (50%) 29 ; however, the respective impact of PE and rituximab could not be assessed, especially because graft survival was observed in about 80% of patients receiving IVIg and PE treatment in the literature.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Only case series were previously reported, and a systematic review of acute AMR treatment published in October 2012 showed insufficient data to guide treatment. 12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29]32 We showed that 1-year graft survival for AMR treated with IVIg, PE, and CS with or without rituximab was excellent, and we could not demonstrate a supplementary efficacy of rituximab by graft survival or our primary endpoint. An additional beneficial effect of PE and rituximab on graft survival was reported in a group of 12 patients receiving IVIg, PE, and rituximab (92%) as compared with a historical group of 12 patients receiving only IVIg (50%) 29 ; however, the respective impact of PE and rituximab could not be assessed, especially because graft survival was observed in about 80% of patients receiving IVIg and PE treatment in the literature.…”
Section: Discussionmentioning
confidence: 89%
“…15 All other reports have been single case reports or case series. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] The findings suggest that rituximab may have some beneficial effects in the treatment of acute AMR along with standard treatment of the condition.…”
mentioning
confidence: 99%
“…Almost all the reports of the use of rituximab as a treatment for acute renal allograft rejection (in addition to a variety of other treatments including plasmapheresis, steroids, OKT3, IVIG, alemtuzumab and ATG) have been purely descriptive, either single‐case reports or case series (see Table ). There has been only one randomized controlled trial: Zarkhin et al .…”
Section: Clinical Use Of Rituximab In Renal Transplantationmentioning
confidence: 99%
“…Almost all the reports of the use of rituximab as a treatment for acute renal allograft rejection (in addition to a variety of other treatments including plasmapheresis, steroids, OKT3, IVIG, alemtuzumab and ATG) have been purely descriptive, either single-case reports [42][43][44][45][46][47] or case series [48][49][50][51][52][53][54][55] (see Table 3). There has been only one randomized controlled trial: Zarkhin et al [56] randomized 20 paediatric patients with biopsy proven acute rejection (BPAR) and a finding of B cell infiltrates in their renal allograft to receive either four doses of rituximab or no additional treatment.…”
Section: Rituximab As a Treatment For Acute Renal Allograft Rejectionmentioning
confidence: 99%
“…In fact, it is expressed in various types of immune cells, including Th1 T cells, Th17 effector T cells, activated B cells, and activated dendritic cells. [19][20][21] In this report, we presented a patient who had acute cellular rejection that was resistant to conventional antirejection therapy. Rejection was successfully reversed with specific monoclonal antibodies against CD20.…”
mentioning
confidence: 99%